A cell culture of the human intervertebral disk - Malyshkina, Svitlana; Kostytska, Olga; Bengus, Lyudmila; Vishnyakova, Iryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2011)
The authors studied a possibility to cultivate cells, isolated from fragments of intervertebral disks, which were removed in patients in the process of reparative-restorative operations on the vertebral column for osteochondrosis. An analysis of the structure of intervertebral disk fragments is presented. Proliferative and biosynthetic abilities of cultured cells were studied with purpose of their use for repairing damaged intervertebral disks.